(untitled) (Third Sector Social Economic Review, 2022)
The intense, competitive and stressful working environments brought by today’s business life cause both managers and employees to be directed by some negative behaviors. Within this context, when managers adopt abusive supervision as a negative approach, this may cause their employees to turn into counterproductive work behavior, and this relationship may differ with workplace ostracism. Therefore the purpose of this study is to examine the moderator role of workplace ostracism on the effect of abusive supervision on counterproductive work behavior. Within the scope of the findings, it’s aimed to explore the causes of negative work behaviors and to contribute to the related literature by developing both managerial and practical suggestions. Questionnaire technique was chosen as the data collection method for this research. The data were collected through a survey technique from 274 people working in businesses operating in the fields of banking, tourism and health in Istanbul. Correlation analysis and hierarchical regression analysis were used to test the research hypotheses. As a result of the research, abusive supervision has a positive and significant effect on counterproductive work behavior and it has been concluded that workplace ostracism plays a moderator role on the effect of abusive supervision on counterproductive work behavior.